A sense of forgetting and remembering: Memories of smell and clothing. Issue 3 (1st December 2018) - Macindoe, Julie
This article gives focus to the residue of smell in the everyday, dressed experience. Through collected narratives and memories, the research uncovers some of the personal and shared practices in negotiating smell and clothing: The smell of a father's jacket acts as a reconciliation, and in its transferral of ownership, constructs an identity. A jumper, sprayed with the promise and artifice of fragrance, forms an aroma of deception to negate a visual appearance. And a traveller's wardrobe reminds that smelly clothing is not a socially neutral experience but a negotiation of our sense of self. Embedding smell in the material context of clothing brings smell beyond the fleshy surface to the dressed body, provoking decisions to forget or remember the body that once inhabited its materiality.